Association of Cardiovascular Disease Risk Factors With Estimated Dietary Salt Consumption in Bangladeshi Adults: A Nationally Representative Cross‐Sectional Study - Lingkan Barua; Tahmina Akhter; Rijwan Bhuiyan; Halima Akter Sathi; Palash Chandra Banik; Mithila Faruque; Muhammad Aziz Rahman; Sheikh Mohammed Shariful Islam (The Journal of Clinical Hypertension)
ABSTRACT This population‐based, nationally representative cross‐sectional study assessed the daily salt consumption status and its associated cardiovascular disease (CVD) risk factors using weighted data from the STEPwise approach to noncommunicable disease risk factor surveillance conducted in 2018 in Bangladesh. It included a non‐institutionalized adults’ population of 6189 men and women aged 18–69 years. Their daily salt consumption was estimated using the spot urine sodium concentration following the Tanaka equation and reported according to the standard nomenclature proposed by the World Hypertension League and partner organizations involved in dietary salt reduction. Out of a total of 6189 participants, 2.4% consumed the recommended amount of salt (<5 g/day), 67.8% consumed a high amount of salt (≥5–10 g/day), 27.2% consumed a very high amount of salt (>10–15 g/day), and 2.6% consumed an extremely high amount of salt (>15 g/day). In univariate analysis, a higher than recommended level of salt intake (≥5 g/day) was significantly prevalent among rural residents (high = 78.4%, very‐high = 81.6%, extremely‐high = 84.9%, p = 0.01), literates (high = 51.6%, very‐high = 57.9%, extremely‐high = 59.1%, p = 0.02), newly diagnosed hypertension (high = 20.6%, very‐high = 23.6%, extremely‐high = 24.1%, p = 0.008), and overweight/obese (high = 25.9%, very‐high = 33.3%, extremely‐high = 29.8%, p = 0.000). Similarly, in ordinal logistic regression analysis, the categories of daily salt consumption showed a significant association with rural residence (OR: 1.300, CI: 1.109–1.524, p = 0.001), literates (OR: 0.777, CI: 0.671–0.900, p = 0.001), newly diagnosed hypertension (OR: 1.204, CI: 1.022–1.419, p = 0.026), and overweight/obesity (OR: 1.353, CI: 1.145–1.598, p = 0.000). The current national pattern of salt consumption in Bangladesh may help reconstruct the salt reduction strategy considering the associated risk factors.